Results data of the regression and correlation analysis of the concentration of germanium with thickness and ashity in the coal seam C 8Н of the Dniprovska mine - Ishkov, Valerii; Kozii, Yevhen; Chernobuk, Oleksandr; Lozovyi, Andrii; Diachkov, Pavlo (Graz, 2022)
For an objective geological and economic assessment of the possibility of simultaneous extraction of germanium from coal, waste and products of its processing and planning of the most effective organizational and technical measures in this regard, it is first of all necessary to have information about the character of the distribution and concentration level of this element in coal and coal-bearing rocks. In order to obtain such information, detailed studies of the distribution of germanium over the area and in the cross-section of the coal seam с8 н of "Dniprovska" mine field were carried out
Keywords: small elements; toxic and potentially toxic elements; sorption optimum; germanium; zone of enrichment